Genetic variants associated with circulating liver injury markers in Mexican Americans, a population at risk for non-alcoholic fatty liver disease - Sabotta, Caroline M.; Kwan, Suet-Ying; Petty, Lauren E.; Below, Jennifer E.; Joon, Aron; Wei, Peng; Fisher-Hoch, Susan P.; McCormick, Joseph B.; Beretta, Laura (Frontiers in Genetics, 2022)
Objective: Mexican Americans are disproportionally affected by non-alcoholic fatty liver disease (NAFLD), liver fibrosis and hepatocellular carcinoma. Noninvasive means to identify those in this population at high risk for these diseases are urgently needed. Approach: The Cameron County Hispanic Cohort (CCHC) is a population-based cohort with high rates of obesity (51%), type 2 diabetes (28%) and NAFLD (49%). In a subgroup of 564 CCHC subjects, we evaluated 339 variants previously reported to be associated with liver injury markers aspartate (AST) and alanine (ALT) aminotransferases in UK and Japanese cohorts. Results: Association was confirmed for 86 variants. Among them, 27 had higher effect allele frequency in the CCHC than in the UK and Japanese cohorts, and 16 had stronger associations with AST and ALT than rs738409 (PNPLA3). These included rs17710008 (MYCT1), rs2519093 (ABO), rs1801690 (APOH), rs10409243 (S1PR2), rs1800759 (LOC100507053) and rs2491441 (RGL1), which were also associated with steatosis and/or liver fibrosis measured by vibration-controlled transient elastography. Main contributors to advanced fibrosis risk were rs11240351 (CNTN2), rs1800759 (LOC100507053), rs738409 (PNPLA3) and rs1801690 (APOH), with advanced fibrosis detected in 37.5% of subjects with 3 of these 4 variants (AOR=11.6 [95% CI]=3.8-35.3). AST- and ALT-associated variants implicated distinct pathways (ethanol and galactose degradation versus antigen presentation and B cell development). Finally, 8 variants, including rs62292950 (DNAJC13), were associated with gut microbiome changes. Conclusion: These genotype-phenotype findings may have utility in risk modeling and disease prevention in this high-risk population.